2022
DOI: 10.3762/bjnano.13.37
|View full text |Cite
|
Sign up to set email alerts
|

Tunable superconducting neurons for networks based on radial basis functions

Abstract: The hardware implementation of signal microprocessors based on superconducting technologies seems relevant for a number of niche tasks where performance and energy efficiency are critically important. In this paper, we consider the basic elements for superconducting neural networks on radial basis functions. We examine the static and dynamic activation functions of the proposed neuron. Special attention is paid to tuning the activation functions to a Gaussian form with relatively large amplitude. For the pract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…It is observed that the superconducting technology-based hardware implementation of signal microprocessors could be useful for a variety of specialized jobs, in which both performance and energy efficiency are of the utmost importance. Within the scope of this research, based on radial basis functions, we examine the essential components of superconducting neural networks (RBF) (Schegolev et al, 2022). Qureshi et al (2014) presented a multiple relay selection scheme for underlay CRN in CSI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is observed that the superconducting technology-based hardware implementation of signal microprocessors could be useful for a variety of specialized jobs, in which both performance and energy efficiency are of the utmost importance. Within the scope of this research, based on radial basis functions, we examine the essential components of superconducting neural networks (RBF) (Schegolev et al, 2022). Qureshi et al (2014) presented a multiple relay selection scheme for underlay CRN in CSI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These elements can significantly help in the design of supercomputers, data centers, neuromorphic circuits, and quantum computing. The use of hybrid structures consisting of superconductors (S) and ferromagnets (F) is one of the modern and promising areas in the development of these devices [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the physical parameter being controlled, SSVs can be divided into three types. These are devices in which a change in the mutual orientation of the magnetic moments of the F-films is accompanied by a variation in their critical current [ 5 , 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], critical temperature [ 26 , 40 , 41 , 42 , 43 , 44 , 45 ], or kinetic inductance [ 4 , 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The roadmap for modern superconducting electronics [ 1 ] classifies the development and study of superconducting spin switches (valves) as one of the promising directions of development. Such devices are necessary for the construction of cryogenic memory elements [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], neuromorphic processors [ 11 , 12 , 13 , 14 , 15 , 16 ], and quantum computers [ 17 , 18 , 19 ] (including those based on the use of quantum optics effects).…”
Section: Introductionmentioning
confidence: 99%